The Role of Maternal Self-efficacy in the Link Between Childhood Maltreatment and Maternal Stress During Transition to Motherhood - Bentley, Gabriella (Journal of interpersonal violence, 2022)
The transition to motherhood is a significant developmental milestone in many women?s lives. This transitional period may be more stressful for women with a history of childhood maltreatment (CM) than for women without such a history. This study tested whether parental self-efficacy (PSE) accounts for the link between CM and parental stress in mothers transitioning to motherhood. The study used a convenience sample of 1,306 first-time mothers of children aged two years or younger. Mothers filled out online self-report questionnaires assessing history of CM, PSE, and prenatal stress. Consistent with the hypotheses, exposure to CM was directly associated with greater parental stress. Also, PSE partially mediated the associations between CM and parental stress, such that mothers with a history of childhood abuse reported a lower level of PSE, which in turn was associated with greater parental stress. In conclusion, the study highlights the important role of negative cognitions related to parenting for maternal dysfunction following exposure to childhood abuse. These findings suggest a need to incorporate preventive interventions designed to promote PSE for mothers exposed to CM. Such programs may alleviate parental stress and further support the healthy development of the child.